Research Status of Gas Turbine Exhaust Diffuser - Bin QIU; Jinglun FU (发电技术)
Gas turbine is the important equipment used in security and economic field of the country. The aerodynamic performance of exhaust diffuser has an important influence on the thermodynamic efficiency of gas turbine. The flow interaction between the exhaust diffuser and the upstream turbine and the complex geometrical configurations leads to the strong vortex pattern and high flow losses in the diffuser which reduces the performance of the upstream turbine and exhaust diffuser. In order to investigate the flow characteristics of diffusers and the coupling mechanism between the diffuser and the turbine, the research status of aerodynamic performance and optimal design of diffusers at home and abroad was reviewed. The prospect of research on the design and optimization of the diffuser was discussed. The interaction between the turbine and the diffuser should be fully considered in future research. Parameterization and other methods were introduced into the optimal design of the diffuser to improve the working efficiency.